Análisis financiero de la empresa “YGA seguridad salud & ambiente CÍA. LTDA., de la ciudad de Loja del periodo 2014-2015 - Amoroso González, Patricia Miroslava (2018)
The present thesis work was carried out in order to comply with the previous requirement to choose the Degree in Accounting and Auditing Engineering, Public Accountant, at the National University of Loja. In addition, it was developed with the purpose of knowing and analyzing the economic and financial situation of the company, providing information for decision-making. For the fulfillment of the objectives a methodology was used that helped to verify the economic and financial situation of the company, which consisted of gathering the information in order to restructure the Financial Statements, apply the vertical, horizontal analysis and the financial indicators, that allowed to determine the liquidity, indebtedness and profitability activity of the years evaluated to establish the situation in which said entity is located. After carrying out the practical part of the financial analysis, the following conclusions were reached, highlighting that the company has economic solvency to face its obligations with third parties, in the same way, its structure reflects that it is liquid, since it has enough current assets to pay off your short-term debts.